Kako geografi, antropologi in literarni teoretiki pripovedujejo o prostorskem obratu - Baskar, Bojan (Primerjalna književnost, 2013)
This paper analyzes a series of emblematic instances of narrating the spatial turn in three disciplines: geography, anthropology, and literary studies. Although the term "spatial turn" itself suggests a transdisciplinary phenomenon, a sort of Zeitgeist that affected a range of disciplines, my analysis, albeit preliminary, discloses a diversity of perceptions, dating, valuation, and motives. Whereas a spatial turn in literary studies is rather obvious, it is paradoxical that such spatially oriented disciplines as geography and anthropology diagnose their spatial turn at all.
Keywords: literarna teorija; literary theory; geografija; geography; anthropology; antropologija; prostor; human settlement; kraj; prostorski obrat; literarne študije